Child mortality in the Hatay - Şahinkaya, Rezan; Kalaycıoğlu, Nermin (The Turkish Journal of Pediatrics, 1962)
1. In the villages of the Hatay the ratio of boys to girls was found to be 110 : 100 in a group of 7215 recorded births. This departure from the 1 : 1 ratio is considered to be statistically significant. 2. In the cities the preponderance of boys was found to be 105 : 100 in a group of 7175 births. This was not considered to be of statistical significance. 3. In the villages, mothers who lived with their husbands until reaching the menopause had an average of 7.804 ± 0.173 confinements resulting in live births and produced on the average 7.928 ± 0.199 live babies. Nearly three-quarters of these women (71.56 per cent) had from 6-10 children, 0.44 per cent had from 1-2 and 0.89 per cent had more than 15. 4. In cities married women living with their husbands until the time of menopause averaged 6.800 ± 0.192 confinements resulting in live births and produced an average of 6.893 ± 0.190 live babies. Of these mothers 59.56 per cent had from 6-10 children, 8.44 per cent had 1-2 and 0.44 per cent had more than 15. 5. The case of one woman was found to be of interest and worth including in the literature since she was a «maximal» case with a record of 19 confinements and 32 live births (13 of which were twins). Unfortunately 28 out of the 32 died before the age of one. 6. The incidence of twins in villages was found to be 1.594 per cent and in cities 1.372 per cent. Both these rates are in accord with world literature. 7. Only 21.78 per cent of village mothers and 32.44 per cent of city mothers lost no children. Among the mothers in the group who had lost children, child deaths averaged 3.090 ± 0.197 per mother in the villages and 2.217 ± 0.117 per city mother (based on children dying before the age of 15.). 8. Child mortality in general for the Hatay was found to be 305/1000 live births in the villages and 217/1000 in the cities. More than half of these deaths, in both villages and cities, occurred before the child reached the age of one year. The rate for infant mortality in the villages was found to be 160/1000 live births and in the cities 120/1000. (These figures reflect the conditions of some 10-15 years ago since they are based on mothers who had already reached the menopause at the time of the study). 9. A smaller survey in 1960 indicated that there had been some improvement with regard to child mortality. In this study the rate of child deaths was found to be 233/1000 in the villages and 138/1000 in the cities which was prorated on the basis of village population equalling 65 per cent of the total population of the region and a general rate of 204/1000 was arrived at. In the villages, 63 per cent of the deaths occurred in the 0 - 1 year age bracket and in cities 86 per cent were found in this age group. The infant mortality rate was thus found to be 147/1000 live births in the villages, 118/1000 in the cities, prorated for a general rate of 137/1000.